PERFORMA GURU DALAM MANAJEMEN KELAS - depri, deprizon (JURNAL ISLAMIKA, 2020)
ABSTRACT This study examines and explores “teacher performance in the classroom management process”. Leadership in learning requires an attractive performance, because the rights and responsibilities carried out and their views towards students are full of compassion, tenderness, this attitude should be part of the value of a teacher's dedication. The author tries to describe the teacher's performance in the classroom management process in educational institutions, namely: (1) describing the policies and educational foundations in the form of classroom and outside learning planning. (2) applying learning components as a system in the teaching and learning process. (3) communicating in professional, social communities and facilitating community learning. (4) managing the class with appropriate approaches and procedures that are relevant to the characteristics of students. (5) researching, developing and innovating in the field of education and learning, and being able to use the results for professional development. This research methodology refers to the library approach (qualitative descriptive library research). This study focuses on the object of study in the form of written theoretical sources. The results of this research, especially for the academic world, can be used as a reference and reference (literature) that can add to the library's treasury, especially in the scientific clusters of Islamic education. Keywords: Performance, Teacher, Class Management.